Intelligent Human Computer Interaction: 9th International Conference, IHCI 2017, Evry, France, December 11-13, 2017, Proceedings - Horain, Patrick; Achard, Catherine; Mallem, Malik (Information Systems and Applications, incl. Internet/Web, and HCI, 2017)
brain computer interface; artificial intelligence; computer networks; classification databases; HCI machine learning; signal processing; user interfaces